2010
DOI: 10.1089/neu.2009.1206
|View full text |Cite
|
Sign up to set email alerts
|

150 Years of Treating Severe Traumatic Brain Injury: A Systematic Review of Progress in Mortality

Abstract: Considerable effort and resources have been devoted to preserving life in patients with severe closed traumatic brain injury (TBI). We sought to identify temporal trends in mortality rates of these patients from the late 1800s to the present. We searched the literature for articles on severe TBI, abstracting numbers of patients studied, numbers of deaths, and years of patient entry. Mortality rates were calculated for each study, and meta-regression was used to pool data and to test for significant temporal tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(130 citation statements)
references
References 178 publications
4
115
0
5
Order By: Relevance
“…It also implies that there has been limited improvement in outcome of TBI over recent years. This finding is in line with a meta-analysis conducted by Stein et al 15 (2010), which showed a steady decline of mortality of approximately 9% per year during the period 1970 to 1990 but no change in mortality rates between 1990 and 2005.…”
Section: Discussionsupporting
confidence: 91%
“…It also implies that there has been limited improvement in outcome of TBI over recent years. This finding is in line with a meta-analysis conducted by Stein et al 15 (2010), which showed a steady decline of mortality of approximately 9% per year during the period 1970 to 1990 but no change in mortality rates between 1990 and 2005.…”
Section: Discussionsupporting
confidence: 91%
“…Mortality rates have not consistently decreased among patients with TBI over the past two decades. 47,48 Conflicting conclusions have been reached among patients with SAH and ICH, although trends have probably been favourable. [49][50][51][52][53] There are relatively few corresponding Canadian data.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the creation of regional trauma referral centers and the introduction of standardized clinical procedures contribute to reduced mortality [3]. Still, severe TBI represent the number one cause of longterm disability for adults and the mortality rate has not declined over the last 10 years [4]. Increasing number of falls in the elderly associated with a high fatality rate in this patient population may outweigh the effects of the overall improvement in TBI management [5].…”
Section: Incidence and Mortalitymentioning
confidence: 99%